Comparison of the therapeutic effects of medication therapy, specific immunotherapy and anti-IgE (Omalizumab) in patients with hay fever - Tang, Rui; Lyu, Xiaohong; Hou, Yibo; Yang, Yongshi; Fu, Guodong; Zhu, Liping; Xue, Lu; Li, Hong; Wang, Ruiqi (Frontiers in Immunology, 2024)
Background: Hay fever, characterized by seasonal allergic reactions, poses a significant health challenge. Existing therapies encompass standard drug regimens, biological agents, and specific immunotherapy. This study aims to assess and compare the effectiveness of anti-IgE (omalizumab), medication therapy, and subcutaneous immunotherapy (SCIT) for hay fever. Methods: Conducted as a retrospective cohort study, this research involved 98 outpatient hay fever patients who underwent routine medication, omalizumab treatment, or SCIT before the onset of the spring pollen season. A follow-up was performed one month after the start of the pollen season. The comprehensive symptoms and drug scores were used to evaluate patients with different intervention methods, facilitating a comparative analysis of therapeutic outcomes. Results: Compared with before treatment, the symptoms of patients treated with the three methods were all significantly relieved, and the medication score were significantly reduced. Patients treated with omalizumab demonstrated higher symptoms and medication scores than SCIT group before treatment, but similar scores after treatment, which were both lower than medicine treatment group. After treatment with omalizumab or SCIT, patients in both groups had significantly lower medication scores than the medication group and were close to no longer using medication for symptom relief. The mountain juniper-sIgE was significantly higher after treatment than before treatment in both medicine treatment group and omalizumab treatment group. Conclusion: Omalizumab and SCIT offer superior effects than medication therapy in hay fever patients.